Middle ear cholesteatoma in children: Retrospective review of Pedro Hispano Hospital - Cruz, Sara (2015)
Middle ear cholesteatoma is a rare disease entity in children. It is an important and rare disease that may have serious consequences.Objectives: Evaluate the results of the ORL Service of Pedro Hispano Hospital (PHH) and analyze the variables associated with the recurrence rate and audiometric results of patients who undergone tympanomastoidectomy for cholesteatoma.Material and Methods: Retrospective review of children under the age of 18 years who had cholesteatoma surgery between 1 January 2001 and 31 December 2011 in PHH.Results: Review of 28 children (30 ears) who had cholesteatoma surgery. 76,7% male, 23,3% female, mean age 10,7 years. Otorrhea and hearing loss are the most common clinical symptoms observed in 76,6% and 40% of children. 56,7% of cholesteatomas were classified as S3, S4 and S5 extension during surgery with ossicular destruction in 80%. Recurrent cholesteatoma was observed in 33,3% ears.Conclusions: Cholesteatoma in children have a more aggressive growth and its diagnosis is often done in more advanced stages. It is important to have a high index of suspicion.